Hubungan Komunikasi Guru Dengan Kecerdasan Emosional Siswa Pada Mata Pelajaran PAI Di SMAN 1 Rao Utara - Dian Martini; Yulia Rahman; Jasmienti Jasmienti; Januar Januar (Pusat Riset dan Inovasi Nasional, 2023)
The aim of this research is to understand the relationship between teacher communication and students’ emotional intelligence in PAI subjects at SMAN 1 Rao Utara. This research was motivated by the low emotional intelligence of students. As a type of research, the author uses correlation research, which is a way to determine the closeness of a relationship between two or more variables which is explained by the magnitude of the correlation coefficient. The population of this research is all students of SMAN 1 Rao Utara, totaling 196 students and a sample of 49 students. The data collection technique for this research is a questionnaire. The results of research condected at SMAN 1 Rao Utara show that there is a relationship between teacher communication and students’ emotional intelligence in PAI subjects of 76.2% 23.8% the influence of other factors, so it can be concluded that there is a relationship between teachers. Communication and emotional intelligence of students. Emotional intelligence of students majoring in PAI at SMAN 1 Rao Utara. Improving teacher communication, namely the ability to perfect teacher communication skills by making changes suvh as attending seminars, reading lots of magazines, studying independently, researching one’s own potential and abilities, participating in various trainings to develop skills, abilities and attitudes related to a teacher’s career and educating students. For ein and to intelligence, namely by knowing their own emotions, controlling their own emotions, encouranging themselves, knowing other people’s emotions and building good relationships.